2007
DOI: 10.1177/1049909106295283
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Interdisciplinary Perceptions of Collaboration on Hospice Teams

Abstract: This project modified the Index for Interdisciplinary Collaboration to create a tool that could measure perceptions of collaboration by all members of the hospice team. Questions on the 42-item instrument were reworded to be more inclusive. This new Modified Index for Interdisciplinary Collaboration (MIIC) showed strong reliability for the total instrument and the original instrument subscales. Further use and testing of this instrument is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 6 publications
0
35
0
2
Order By: Relevance
“…In addition, Oliver et al (2006Oliver et al ( , 2007 explored the measurement of collaboration with all hospice disciplines and identified variances between hospice teams. The five teams in the 2006 study of variance all had high mean MIIC scores indicating positive perceptions of interdisciplinary collaboration but there was also significant variance between teams in total collaboration and on the components interdependence, collective ownership of goals, and reflection on team process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Oliver et al (2006Oliver et al ( , 2007 explored the measurement of collaboration with all hospice disciplines and identified variances between hospice teams. The five teams in the 2006 study of variance all had high mean MIIC scores indicating positive perceptions of interdisciplinary collaboration but there was also significant variance between teams in total collaboration and on the components interdependence, collective ownership of goals, and reflection on team process.…”
Section: Methodsmentioning
confidence: 99%
“…Testing the index demonstrated that it was valid and that it reliably measured social workers' perceptions of team collaboration (Parker-Oliver et al, 2005). The index was modified and validated to explore the perspective of various disciplines as the Modified Index of Interdisciplinary Collaboration (MIIC; Oliver, Wittenberg-Lyles, & Day, 2006& Day, , 2007.…”
Section: Definitions Theoretical Framework and Previous Studies Defmentioning
confidence: 99%
“…Oliver, Wittenberg-Lyles, and Day (2007) identified four markers of interdisciplinary perceptions for hospice. They included a multidisciplinary theory of collaboration, role theory, services integration, and ecological systems theory.…”
Section: Interdisciplinary Teams/gittmentioning
confidence: 99%
“…In addition to mandatory bereavement support, some hospices offer art, massage, or pet therapy. Much research on communication and collaboration has demonstrated the complexity of hospice care the IDT provides (Oliver, Tatum, Kapp, & Wallace, 2010; Oliver, Wittenberg-Lyles, & Day, 2006; Wittenberg-Lyles, Oliver, Demiris, Baldwin, & Regehr, 2008; Wittenberg-Lyles, Oliver, Demiris, & Regehr, 2010). To our knowledge, however, no researchers have specifically explored the setting of hospice care in the United States and its influence on IDT roles and care processes.…”
Section: Roles Of Interdisciplinary Team Membersmentioning
confidence: 99%